The functional and structural changes in the basilar artery due to overpressure blast injury - (:unkn) unknown (SAGE PUBLICATIONS INC, 2015)
Overpressure blast-wave induced brain injury (OBI) leads to progressive pathophysiologic changes resulting in a reduction in brain blood flow, blood brain barrier breakdown, edema, and cerebral ischemia. The aim of this study was to evaluate cerebral vascular function after single and repeated OBI. Male Sprague-Dawley rats were divided into three groups: Control (Naive), single OBI (30 psi peak pressure, 1 to 2 msec duration), and repeated (days 1, 4, and 7) OBI (r-OBI). Rats were killed 24 hours after injury and the basilar artery was isolated, cannulated, and pressurized (90 cm H2O). Vascular responses to potassium chloride (KCl) (30 to 100 mmol/L), endothelin-1 (10(-12) to 10(-7) mol/L), acetylcholine (ACh) (10(-10) to 10(-4) mol/L) and diethylamine-NONO-ate (DEA-NONO-ate) (10(-10) to 10(-4) mol/L) were evaluated. The OBI resulted in an increase in the contractile responses to endothelin and a decrease in the relaxant responses to ACh in both single and r-OBI groups. However, impaired DEA-NONO-ate-induced vasodilation and increased wall thickness to lumen ratio were observed only in the r-OBI group. The endothelin-1 type A (ETA) receptor and endothelial nitric oxide synthase (eNOS) immunoreactivity were significantly enhanced by OBI. These findings indicate that both single and r-OBI impairs cerebral vascular endothelium-dependent dilation, potentially a consequence of endothelial dysfunction and/or vascular remodelling in basilar arteries after OBI.
Keywords: basilar artery; endothelium; endothelin; NO; overpressure blast injury; trauma; TRAUMATIC BRAIN-INJURY; ENDOTHELIAL NO SYNTHASE; SUBARACHNOID HEMORRHAGE; BARRIER PERMEABILITY; OXIDATIVE STRESS; CEREBRAL VASOSPASM; NITRIC-OXIDE; TETRAHYDROBIOPTERIN; INFLAMMATION; PRESSURE